High ambient temperature during a first bout of exercise affects endurance capacity during a second bout of similar exercise - Amada da Silva, P.; Jones, D. A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
performance during subsequent exercise and how any such effects are affected by different ambient conditions during the first bout of exercise. Methods Seven endurance-trained men performed three trials that included an exhausting cycling exercise at an ambient temperature of 35 ºC, starting at 12:00 AM, combining 60 min at a workload of 60% that was increased to 65% during the next 15 min and then to 70%, a workload that was maintained until exhaustion. On one occasion the exhausting exercise was preceded by rest (ONE) while in the other two trials a 60 min cycling exercise at 60%, starting at 09:00 AM was carried out, both in a cool (21ºC, TWOCOOL) and a hot environment (35ºC, TWOHOT). Rectal temperature and skin temperatures from the head, hand, leg and lower back were measured during exercise. Blood samples for measurements of plasma concentrations of glucose, lactate and prolactin were taken at the start of exercise and every 30 min during exercise, at exhaustion (afternoon exercises) and during the first 30 min recovery. Results Time to exhaustion in the TWOHOT trial was significantly lower when compared to ONE trial [67.32 ± 4.38 (SEM) vs. 77.54 ± 4.29 min, P < 0.05] whereas in the TWOCOOL trial, time to exhaustion was similar to those of the other two trials (69.47± 2.41 min). Rectal temperature (Tre) at the start and throughout the afternoon exercise was identical between trials, and at exhaustion average Tre was 39.04 ± 0.23, 38.82 ± 0.17 and 38.86 ± 0.26 ºC in ONE, TWOCOOL and TWOHOT trials, respectively (P < 0.05). In the afternoon exercise, no significant differences existed in mean skin temperature, sweat rate, heart rate, ratings of perceived exertion (RPE), thermal comfort, and plasma levels of glucose. Plasma lactate was lower at 30 min of exercise in the TWOCOOL trial, whereas plasma prolactin accumulation at exhaustion was lower in the TWOHOT trial, both compared to the ONE trial. Discussion/Conclusion It is concluded that high ambient temperature during a first bout of exercise reduced the capacity to exercise during a subsequent exercise in the heat more than was the case with exercise at room temperature. Since no metabolic changes were clearly noticed as a result of repeating exercise and that great care was taken to prevent dehydration throughout the entire experimental protocol, it is suggested that impaired performance due to prior exercise in the heat is better explained by decreased tolerance to the rise of body temperature.